Offshoring and Labor Markets - David Hummels; Jakob R. Munch; Chong Xiang (Institute for the Study of Labor (IZA), 2016)
In this paper we survey the recent empirical literature on the effects of offshoring on wage, employment and displacement. We start with an overview of the measurement of offshoring, organizing our discussion around the three key elements of offshoring: that it involves intermediate inputs for production (vs. final goods for consumption); that it involves imported inputs (vs. domestically produced ones); and that the inputs involved could have been produced internally within the same firm. We then briefly discuss the theories of offshoring, and survey the literature that examines the wage effects of offshoring: the wave of studies using industry-level data; the wave using firm-level data; the wave using worker-level data; and the wave using matched worker-firm data. For each wave we highlight the identification strategies used, critically assess its strength and weakness, discuss its connections with theory, and draw out potential policy implications of its findings. Finally we survey the literature that examines how offshoring affects employment and displacement. We highlight the recent development of a novel cohort-based approach that is specifically designed to address selection with displacement, and capable of identifying the overall effects of offshoring, including wage, displacement, and all other types of transition.
Keywords: F1; J2; J3; L2; 330; offshoring; wages; unemployment